2010
DOI: 10.3382/ps.2010-00709
|View full text |Cite
|
Sign up to set email alerts
|

Changes in selected biochemical indices related to transport of broilers to slaughterhouse under different ambient temperatures

Abstract: The effect of transport distance on selected biochemical parameters (corticosterone, uric acid, triglycerides, total protein, glucose, and lactate) under various ambient temperatures was monitored in a group of unsexed Ross 308 broilers aged 42 d. Broilers were transported to the slaughterhouse over 3 different travel distances (10, 70, and 130 km). They were sampled before and after each transportation in 3 various periods with different ambient temperatures (-5 to +5°C, 10 to 20°C, and 25 to 35°C), which app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 23 publications
9
53
2
2
Order By: Relevance
“…Zhang et al reported that blood glucose increased for short time transport, which was supplied by liver glycogen and a 3 h transport could decrease plasma glucose level, because of the exhaustion of liver glycogen [16]. Similar reductions of glucose following long transport duration were also found by Suchy et al, Sarkar et al and Vosmerova et al [20,21,23]. When the breakdown of liver glycogen could not make up for the shortage of glucose, animal body initiates the use of fat and protein.…”
Section: Transport Durationsupporting
confidence: 67%
See 1 more Smart Citation
“…Zhang et al reported that blood glucose increased for short time transport, which was supplied by liver glycogen and a 3 h transport could decrease plasma glucose level, because of the exhaustion of liver glycogen [16]. Similar reductions of glucose following long transport duration were also found by Suchy et al, Sarkar et al and Vosmerova et al [20,21,23]. When the breakdown of liver glycogen could not make up for the shortage of glucose, animal body initiates the use of fat and protein.…”
Section: Transport Durationsupporting
confidence: 67%
“…Consequently, the increasing of HL ratio is a reliable and steady parameter reflecting poultry transport stress [6,18,19]. Transport duration could considerably affect plasma glucose level [16,[20][21][22]. Zhang et al reported that blood glucose increased for short time transport, which was supplied by liver glycogen and a 3 h transport could decrease plasma glucose level, because of the exhaustion of liver glycogen [16].…”
Section: Transport Durationmentioning
confidence: 99%
“…Several studies have considered the effect of transportation duration and distance on animal welfare and resultant meat quality of broiler chickens. However, the reports are contradictory, where the majority of studies have associated long-term transportation to higher mortalities (Nijdam et al, 2004;Vecerek, Grbalova, Voslarova, Janackova, & Malena, 2006;Vieira, Silva, Barbosa Filho, Vieira, & Broom, 2011;Vieira, Silva, Barbosa Filho, Vieira, Rodrigues-Sarnighausen, et al, 2011;Warriss, Bevis, & Brown, 1990;Whiting et al, 2007), but some have indicated that short-term transportation could be more stressful to the birds (Vosmerova et al, 2010). Nijdam et al (2004) reported an increase of 6% in DOA for each additional 15 min in transportation time and an additional increase of 3% for each extra 15 min in lairage time based on transport of 1907 Dutch and German broiler flocks, and concluded that the concurrent effect of temperature and journey duration is an important determinant of DOA.…”
Section: Transport Duration and Distancementioning
confidence: 93%
“…According to Whiting et al (2007), travel time plays an important role in DOA rates, where the combination of time of slaughter, shrink and travel time accounted for 10.5% of the variability in the DOA rate. On the contrary, Vosmerova et al (2010) pointed out that shorter transportation duration might be more stressful to the birds, because they do not have enough time to recover from the stress induced during handling and crating, which was shown to be the highest of all sources of stress. Silva, Simoes, Rossa, Ida, and Shimokomaki (2011) did not find any effect of transportation distances of 15 to 57 km on DOA rates during winter transportation.…”
Section: Transport Duration and Distancementioning
confidence: 93%
“…Yaman et al (2000) described similar triacylglycerol pattern in growing feed-deprived chicks while plasma cholesterol was not influenced. Triacylglycerol concentration was decreased with travel distance at summer temperature (Vosmerova et al, 2010). Moraes et al (2003) suggested that reduction in plasma triacylglycerol may be a consequence of some mechanism which enhances thermotolerance of broilers.…”
Section: Discussionmentioning
confidence: 99%